Nutritional Relationships in Bitter Pit-Affected Fruit and the Feasibility of Vis-NIR Models to Determine Calcium Concentration in ‘Fuji’ Apples - Claudia Bonomelli; René Mogollón; Sergio Tonetto de Freitas; Juan Pablo Zoffoli; Carolina Contreras (Agronomy, 2020)
‘Fuji’ is among the most cultivated apples worldwide but affected by the disorder bitter pit (BP). Calcium deficiency plays an important role on fruit susceptibility to BP. The objectives of this study were to determine nutritional relationships in BP-affected fruit and to verify if Vis-NIR models can predict Ca concentration in ‘Fuji’ apples. Fruit was harvested during 2018 season from two different orchards with historical high BP incidence. Seven hundred and fifty apples were stored at 0 °C for 150 days plus 10 days at 20 °C for BP assessments. After storage, 20 fruit with BP symptoms (BP+) and 20 healthy fruit (BP−) were assessed individually for mineral concentration. Vis-NIR evaluation involved a spectra range from 285 to 1200 nm to predict Ca concentration from ‘Fuji’ powder enriched Ca solutions. In each orchard, healthy apples had significantly higher Ca concentration than apples with BP. The K/Ca and Mg/Ca ratios were significantly lower in healthy fruit compared with BP− affected fruit. The relationship B/Ca proved to be significant in BP fruit. Although Ca interaction with organic substances and/or cellular structures could influence NIR spectra in fresh fruit, our results showed that Vis-NIR models could not be used to direct prediction of fruit Ca concentration.